Physical and biogenic complexity mediates ecosystem functions in urban sessile marine communities. Issue 3 (5th January 2023) - Mayer‐Pinto, Mariana; Bugnot, Ana B.; Johnston, Emma L.; Potts, Jaimie; Airoldi, Laura; Glasby, Tim M.; Strain, Elisabeth M. A.; Scanes, Peter; Ushiama, Shinjiro; Dafforn, Katherine A.
Abstract: The influence of habitat complexity on biodiversity is a central theme in ecology, with many studies reporting positive relationships. Reconciliation approaches in urbanised areas, such as eco‐engineering, have increasingly focused on 're‐building' the complexity of degraded and/or homogenised habitats to support biodiversity. Yet, the effects of increasing complexity and biodiversity on ecological functions are rarely measured. We assessed how increasing the physical and/or biogenic complexity of habitats affects the net primary productivity (NPP) and gross primary productivity (GPP), community respiration and nutrient cycling (specifically dissolved inorganic phosphorus and nitrogen) of intertidal sessile marine communities at three sites. We manipulated physical complexity using two types of settlement tiles: 'complex', with crevices and ridges, and 'flat'. We increased biogenic complexity on half the replicates of each tile type by seeding with oysters. Increased physical and biogenic complexity resulted in greater sessile species richness at all sites. Although many variables assessed varied with sites and time of measurements, overall, GPP and NPP were greater on flat tiles than on complex ones. These patterns were not explained by differences in the total surface area of tiles. Daily flux rates of dissolved inorganic phosphorus had a significant positive relationship with biogenic complexity. There were no effects of biogenic or physical complexity on the net fluxes of dissolved inorganic nitrogen. Effects of habitat complexity on the productivity and nutrient cycling of marine sessile communities were largely unrelated to diversity measures, such as richness or abundance of key taxa and functional groups. Synthesis and applications . Eco‐engineering practices that manipulate habitat complexity might benefit from explicit functional targets that also consider associated ecosystem services, as we found that under some conditions there is a trade‐off between biodiversity and functional targets. Our results suggest that increasing habitat complexity has a positive effect on sessile species richness, but not necessarily on productivity (GPP and NPP). The species pool available as well as light availability is likely to mediate effects of complexity on assemblages, so local environment needs to be a key consideration when designing interventions. Abstract : Eco‐engineering practices that manipulate habitat complexity might benefit from explicit functional targets that also consider associated ecosystem services, as we found that under some conditions there is a trade‐off between biodiversity and functional targets. Our results suggest that increasing habitat complexity has a positive effect on sessile species richness, but not necessarily on productivity (GPP and NPP). The species pool available as well as light availability is likely to mediate effects of complexity on assemblages, so local environment needs to be a key consideration when designing interventions.